The Integration of the Requirements and Characters of the Pupuh in the Wawacan Panji Wulung Manuscript - Elis Suryani Nani Sumarlina; Rangga Saptya Mohamad Permana; Undang Ahmad Darsa; Abdul Rasyad; Wina Erwina (Universitas Hamzanwadi, 2025)
Manuscripts, as a legacy and cultural inheritance of predecessors, are vital cultural documents for the advancement of a society's culture. Consequently, manuscripts must not be undervalued. This is comprehensible, as their existence can still be realized in the Generation Z age. The important and interesting manuscripts studied in this article are manuscripts in the Sundanese literature category in the form of Wawacan, which is closely related to pupuh. Wawacan has an influence on the Sundanese literary treasury. The purpose of this study is to explain the definition, position and classification, as well as the requirements and character of pupuh in an effort to support understanding of the ins and outs of WPW. This article's examination of the literary elements aims to offer an overview, context, and elucidation of the Wawacan Panji Wulung text, which was widely esteemed and utilized as an educational reference, culminating in six print editions during its era. This article is part of qualitative research, employing descriptive analysis methodologies through sociological literary approaches, hermeneutics, which are intrinsically linked to philological studies, both codicologically and textologically, as well as cultural studies in general. The study's results demonstrate the interconnection between the requirements and characteristics of the pupuh, together with the complexities of Wawacan Panji Wulung. This page serves as a reference for literacy across several scientific disciplines in a multidisciplinary context.